Mortality of workers employed at organochlorine pesticide manufacturing plants--an update. - Brown, David P. (Scandinavian Journal of Work, Environment & Health, 1992)
A previous mortality study among four organochlorine pesticide manufacturers was updated through 1987. The organochlorine pesticides included chlordane; heptachlor and endrin; aldrin, dieldrin and endrin; and dichlorodiphenyltrichloroethane. The mortality for all causes and all malignant neoplasms at each of the plants was lower than expected. There was a statistically significant increase in liver and biliary tract cancer among workers at plant 3 (5 observed, standardized mortality ratio 393, 95% confidence interval 1.27-9.20). These results are somewhat consistent with experimental animal findings showing benign and malignant tumors of the liver after exposure to aldrin and dieldrin. However, the deaths were due to a mixture of intra- and extra-hepatic tumors, and the dose-response analysis was limited because of the small number of deaths and lack of exposure data. Additional study of this group should include continued follow-up of the total cohort and a case-referent analysis of the deaths from liver and biliary tract cancer.